SISTEM REMOTING PADA AIR CONDITIONER BERBASIS WEB SERVER - Rizki Pratomo; Ghiri Basuki Putra; Muhammad Jumnahdi (TESLA: Jurnal Teknik Elektro, 2023)
The remoting system on a web server-based Air Conditioner is a system that can make it easier to control the Air Conditioner from anywhere. The problem in this study is that in the student learning activity room in the Electrical Engineering Laboratory, Faculty of Engineering, University of Bangka Belitung, there is no longer an Air Conditioner remote that can be used, because it is lost, damaged, and so on. This becomes an obstacle when you want to use an Air Conditioner. With this control system tool it can facilitate the use of Air Conditioners in the Electrical Engineering laboratory learning room. The components needed to create this control system are NodeMCU ESP8266, DHT22 temperature sensor, LDR sensor, relay module, breadboard, I2C LCD, modified remote air conditioner, PC817 optocoupler and jumper cables. Commands given via the web server will produce a high output for the remote signal via the PC817 optocoupler. The PC817 optocoupler is used to produce logic 1 (on) on the remote Air Conditioner which is modified in such a way that it can work on this control system. From the results of the control system data collection, the average value of the speed of sending orders to the reference room is 10.01 seconds and the workshop room is 10.59 seconds. The average difference between room temperature and air conditioning temperature from the DHT22 sensor for the reference room is 7.71°C and for the workshop room is 5.16°C. The average difference between the web server temperature set and the Air Conditioner temperature also gets a different value, namely in the reference room it is 1.46°C and in the workshop room it is 1.42°C. The average speed of the LDR sensor working in the reference room is 8.60 seconds and the reference room is 7.57 seconds. ABSTRAK: Sistem remoting pada Air Conditioner berbasis web server merupakan sistem yang dapat mempermudah mengendalikan Air Conditioner dari mana saja. Permasalahan dalam penelitian ini yaitu pada ruangan kegiatan belajar mahasiswa di laboratorium jurusan Elektro Fakultas Teknik Universitas Bangka  Belitung tidak lagi terdapat remot Air Conditioner yang bisa digunakan, dikarenakan hilang, rusak dan lain sebagainya. Hal ini menjadi kendala ketika ingin menggunakan Air Conditioner. Dengan adanya alat sistem kendali ini dapat mempermudah penggunaan Air Conditioner pada ruangan pembelajaran laboratorium Teknik Elektro. Komponen yang dibutuhkan untuk membuat sistem alat kendali ini berupa NodeMCU ESP8266, Sensor suhu DHT22, Sensor LDR, Modul Relay, Breadboard, LCD I2C, Remot Air Conditioner yang dimodifikasi, Optocoupler PC817 dan kabel jumper. Perintah yang diberikan melalui web server akan menghasilkan output high untuk sinyal remot melalui optocoupler PC817. Optocoupler PC817 digunakan untuk menghasilkan logika 1 (on) pada remot Air Conditioner yang dimodifikasi sedemikian rupa agar bisa bekerja pada sistem kendali ini. Dari hasil pengambilan data sistem kendali, untuk nilai rata-rata kecepatan pengiriman perintah pada ruangan referensi bernilai 10,01 second dan ruangan workshop bernilai 10,59 second. Rata-rata selisih suhu ruangan dan suhu Air Conditioner dari sensor DHT22 untuk ruangan referensi bernilai 7,71°C dan ruangan workshop bernilai 5,16°C. Rata-rata selisih set suhu web server dengan suhu Air Conditioner mendapatkan nilai yang berbeda juga yaitu pada ruangan referensi bernilai 1,46°C dan ruangan workshop bernilai 1,42°C. Rata-rata kecepatan sensor LDR bekerja pada ruangan referensi benilai 8,60 second dan ruangan referensi bernilai 7,57 second